The centrifugal state: In search of an explanation of why countries decentralise - Rodríguez-Pose, Andrés (Quaestiones Geographicae, 2024)
Nation-states across the world are increasingly relinquishing powers to subnational tiers of government. This paper examines the drivers of this decentralisation revolution and the forces propelling it. While conventional wisdom has long attributed this phenomenon to the triumvirate of democracy, economic efficiency, and regional identity, the contemporary dynamics presented in this paper demand a far more nuanced interpretation. Through the dual lenses of the efficiency-based decentralisation theorem and political economy analysis, I discuss how globalisation, technological upheaval, and innovations in governance have fundamentally reshaped the relationship between political centres and periphery within countries. The empirical evidence reveals decentralisation not as a linear progression but as an intricate interweaving of economic imperatives and political will. This complexity defies simple causation, suggesting instead that the dispersal of power responds to an elaborate choreography of classical and modern forces. The paper dwells on the subtle mechanics of governmental reorganisation, offering insights into the evolving architecture of multi-level governance while acknowledging the inherent challenges in isolating singular causes for these transformative trends.